Long non-coding RNA-H19 antagonism protects against renal fibrosis - Xie, Hong (Oncotarget, 2016)
Although long non-coding RNAs (lncRNAs) are important players in the initiation and progression of many pathological processes, the role of lncRNAs in renal fibrosis still remains unclear. We showed that lncRNA-H19 expression was significantly up-regulated in TGF-β2-induced HK-2 cell fibrosis and unilateral ureteral obstruction (UUO)-induced renal fibrosis in vivo. H19 knockdown significantly attenuated renal fibrosis in vitro and in vivo. LncRNA-H19, miR-17, and fibronectin constituted to a regulatory network involved in renal fibrosis. We also detected up-regulated H19 expression and down-regulated miR-17 expression in the early and advanced animal models of renal fibrosis. This study indicates that H19 up-regulation contributes to renal fibrosis. H19 inhibition might represent a novel anti-fibrotic treatment in renal diseases.